Quadruple Target Evaluation of Diversity-Optimized Halogen-Enriched Fragments (HEFLibs) Reveals Substantial Ligand Efficiency for AP2-Associated Protein Kinase 1 (AAK1) - Dammann, Marcel; Kramer, Markus; Zimmermann, Markus O.; Boeckler, Frank M. (Frontiers in Chemistry, 2022)
Fragment based drug discovery is one of the most utilized approaches for the identification of novel weakly binding ligands, by efficiently covering a wide chemical space with rather few compounds and by allowing more diverse binding modes to be found. This approach has led to various clinical candidates and approved drugs. Halogen bonding on the other hand, has gained traction in molecular design and lead optimization, but could offer additional benefits in early drug discovery. Screening halogen-enriched fragments (HEFLibs) could alleviate problems associated with the late introduction of such a highly geometry dependent interaction. Usually, the binding mode is then already dominated by other strong interactions. Due to the fewer competing interactions in fragments, the halogen bond should more often act as an anchor point for the binding mode. Previously, we proposed a fragment library with a focus on divers binding modes that involve halogens for gaining initial affinity and selectivity. Herein, we demonstrate the applicability of these HEFLibs with a small set of diverse enzymes: the histone-lysine N-methyltransferase DOT1L, the indoleamine 2,3-dioxygenase 1 (IDO1), the AP2-associated protein kinase 1 (AAK1), and the Calcium/calmodulin-dependent protein kinase type 1G (CAMK1G). We were able to identify various binding fragments via STD-NMR. Using ITC to verify these initial hits, we determined affinities for many of these fragments. The best binding fragments exhibit affinities in the one-digit micromolar range and ligand efficiencies up to 0.83 for AAK1. A small set of analogues was used to study structure-affinity relationships and hereby analyze the specific importance of each polar interaction. This data clearly suggests that the halogen bond is the most important interaction of fragment 9595 with AAK1.